Enhancing Gen Z's Digital Financial Inclusion through Interactive Flipbooks and Contextual Learning: A Participatory Action Research - Amalina, Endah Nur; Astriani, Erni; Jawanoko, Nashru Aji; Afdhila, Qory; Prastika, Titis Dwi; Fibrianti, Triska Aulia; Lestari, Wahyu Putri; Nurfadilla, Yunika; Ghofur, Muhammad Abdul; Yusida, Ermita (Mitra Edukasi dan Publikasi, 2025)
The low financial inclusion index among 15–17-year-olds, at only 57.96%, highlights an urgent need for targeted interventions. Financial inclusion is an important factor in the growth and development of a country, as well as a driver of the achievement of the SDGs. Therefore, community service activities were carried out focused to increase Gen Z's understanding and active participation in financial services. This community service activity uses the Participatory Action Research (PAR) method, which consists of five stages: Research and Intervention Goals, Assessment of Needs, Action Planning, Action Taking, and Project Outcomes. A total of 427 tenth-grade students from senior high school in Surabaya participated. Interventions included the development and classroom use of interactive flipbooks on Central Banking, Payment Systems, and Payment Instruments, combined with contextual learning activities such as financial education sessions with Bank Indonesia, bank account openings, and hands-on digital transactions (e.g., QRIS, e-wallets, and mobile banking) during a school entrepreneurship bazaar. Data were collected through pre- and post-tests, structured questionnaires, interviews, and behavioral observations. Quantitative analysis was used to measure cognitive gains (test scores) and behavioral indicators (account openings and digital transaction frequency). The results showed a significant increase in students’ knowledge and participation in formal financial systems. The combination of interactive digital media and contextual experiential learning effectively bridged the gap between Gen Z’s digital potential and their financial inclusion. This model can be scaled nationally to support inclusive economic development among youth.